Handbook of Non-Ferrous Metal Powders : Technologies and Applications. - Neĭkov, Oleg Domianovich (Elsevier, 2009)
A heavyweight classic from the Ukraine and Russia: everything on non-ferrous metal powders.
Keywords: Powder metallurgy -- Handbooks, manuals, etc.; Nonferrous metals -- Handbooks, manuals, etc.; Powder metallurgy.; Nonferrous metals -- Metallurgy.; Powder metallurgy -- Equipment and supplies.; Metal powders.; elektronické knihy; electronic books